Waste heat recovery in the EU Industry and proposed new technologies - Agathokleous, Rafaela; Bianchi, Giuseppe; Panayiotou, Gregoris; Aresti, Lazaros; Georgiou, Georgios C.; Tassou, Savvas A.; Kalogirou, Soteris A.; Florides, Georgios A.; Christodoulides, Paul (My University, 2019)
In the European Union (EU), industrial sectors use 26% of the primary energy consumption and are characterized by large amounts of energy losses in the form of waste heat at different temperature levels. Their recovery is a challenge but also an opportunity for science and business. In this study, after a brief description of the conventional Waste Heat Recovery (WHR) approaches, the novel technologies under development within the I-ThERM Horizon 2020 project are presented and assessed from an energy and market perspectives. These technologies are: heat to power conversion systems based on bottoming thermodynamic cycles (Trilateral Flash Cycle for low grade waste heat and Joule-Brayton cycle working with supercritical carbon dioxide for high temperature waste heat sources); heat recovery devices based on heat pipes (flat heat pipe for high grade radiative heat sources and condensing economizer for acidic effluents).
Keywords: Energy recovery; Heat pipe; Supercritical CO2; Trilateral Flash Cycle; Waste heat recovery